2019
DOI: 10.1371/journal.pone.0221389
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and treatment of acute respiratory illness in children under five in primary care in low-, middle-, and high-income countries: A descriptive FRESH AIR study

Abstract: BackgroundRespiratory disease and, specifically, pneumonia, is the major cause of mortality and morbidity in young children. Diagnosis of both pneumonia and asthma in primary care rests principally on clinical signs, history taking, and bronchodilator responsiveness. This study aimed to describe clinical practices in diverse global primary care settings concerning differential diagnosis of respiratory disease in young children, especially between pneumonia and asthma.MethodsHealth professionals in Greece, Kyrg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Most studies were conducted in lower-middle-or upper-middle-income countries (22 and 19, respectively), while only 6 were in a low-income country. Additionally, 1 study was carried out in 3 countries (1 low income and 2 lower-middle income) [70]. Both public and private healthcare services were involved in 10 of the 48 (20.8%) included studies, whereas 26 (54.2%) studies were focused on the public sector, 4 (8.3%) were focused on the private sector, and 8 (16.7%) did not provide this information; none of the studies mentioned any involvement of informal practitioners.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in lower-middle-or upper-middle-income countries (22 and 19, respectively), while only 6 were in a low-income country. Additionally, 1 study was carried out in 3 countries (1 low income and 2 lower-middle income) [70]. Both public and private healthcare services were involved in 10 of the 48 (20.8%) included studies, whereas 26 (54.2%) studies were focused on the public sector, 4 (8.3%) were focused on the private sector, and 8 (16.7%) did not provide this information; none of the studies mentioned any involvement of informal practitioners.…”
Section: Resultsmentioning
confidence: 99%
“…Inappropriate care for these common childhood infections has been described by other researchers in Uganda and other LMICs. Mbonye et al in their research among private clinics and drug shops found that children with normal respiratory rates received unnecessary antibiotics for pneumonia [44], while Kjaergaad et al found inappropriate prescription rate of antibiotics for viral upper respiratory tract infections of 23-68% in Uganda and other countries across the globe [45]. Other studies carried out in private and public health facilities in Uganda and other African countries found that 7-24% children testing positive for malaria never received the correct malaria medicine [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The The two specific Health Centre IV were selected for this study based on prior research indicating that (1) adherence to IMCI was low, (2) consultations were performed by health workers with limited training, (3) antibiotics were overprescribed and (4) inhaled bronchodilators for wheezing illness were not prescribed. 9…”
Section: Study Sitesmentioning
confidence: 99%